Acceleration of the Extreme Sea Level Rise Along the Chinese Coast. Issue 10 (23rd October 2019) - Feng, Jianlong; Li, Delei; Wang, Tao; Liu, Qiulin; Deng, Lijing; Zhao, Liang
Abstract: Using high‐frequency tide gauge observations from 1980 to 2017, we analyzed changes in extreme sea levels (ESLs) along the Chinese coast to examine whether extreme sea‐level rise acceleration could be observed. The results indicated that the ESL has risen with fluctuations along the Chinese coast. The ESL also featured significant decadal variabilities. The ESL rise was accelerated at most tide gauges throughout the whole study period, especially after the 1980s, while the acceleration patterns varied with station location. The mean sea level (MSL) change was confirmed as the major driver of the ESL change according to the analysis. However, the skew surge may also have affected the extremes at many of the tide gauges, which was observed after detrending. The extreme/MSL had a significant positive correlation with the Atlantic Multidecadal Oscillation, which is supposed to affect the MSL through a combination of variation in sea surface temperature, pressure system, and wind. That sea level oscillation is dominated by Atlantic Multidecadal Oscillation should be taken into consideration when studying accelerations in the rate of ESLs and of MSLs along the Chinese coast. Key Points: The acceraction of the extreme sea level along the Chinese coast is analyzed in the paper for the first time We found that the Atlantic Multidecadal Oscillation (AMO) significantly affect the mean sea levels and extreme sea levels along the Chinese coast